Quantification of beta-defensins (DEFB) gene copy number variations in relation to inflammation in type 2 diabetes mellitus and diabetic nephropathy patients - Yusoff, Maryam Jamielah; Abd Rahim, Zahirunisa; Ghazi, Nurul Amiera; Chin, Shi Kee; Yahya, Mohd Jokha; Adam, Noor Lita; Ismail, Patimah; Abu Bakar @ Jamaludin, Suhaili (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Association studies between single nucleotide polymorphisms (SNPs) and type 2 diabetes mellitus (T2DM) have been abundant. However, there are limited reports on copy number variations (CNVs) of beta-defensins (DEFB) gene in relation to T2DM. In this study, DEFB copy numbers were quantified in T2DM with nephropathy, T2DM without nephropathy and non-diabetic control groups to investigate its influence in chronic inflammation in Malaysian individuals. Methods: DEFB copy number in Malaysian individuals were quantified by using paralogue ratio tests (PRT) which allow direct quantification of gene copy number by using PRT107A and HSPD21 PRT primers. The copy number generated was then validated from insertion/deletion ratio measurement 5DEL (rs5889219) and two microsatellite analyses (EPEV-1 and EPEV-3). Results: DEFB copy number was found extending from 2 to 8 copies in the non-diabetic group (n=146), while in T2DM group (n=392), copy numbers were more extensive, ranging between 1 and 12 copies; with 1, 10 and 12 copies detected in T2DM with nephropathy group (n=202). Statistically, there is no significant difference in DEFB copy number between T2DM and the non-diabetic group (p=0.209) as well as between diabetic nephropathy and without nephropathy of the T2DM group (p=0.522). However, significant white blood cell (WBC) count was found between T2DM groups with and without diabetic nephropathy (p=0.000). Conclusion: Extreme DEFB copy numbers in T2DM with nephropathy group suggest future studies with bigger sample size are necessary to elucidate the true impact of CNVs of DEFB gene in promoting early onset of nephropathy in T2DM.